2020
DOI: 10.1029/2020gl088893
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change Significantly Alters Future Wildfire Mitigation Opportunities in Southeastern Australia

Abstract: Prescribed burning is used globally to mitigate the risks of wildfires, with severe wildfires increasing in frequency in recent decades. Despite their importance in wildfire management, the nature of future changes to prescribed burn windows under global warming remains uncertain. We use a regional climate projection ensemble to provide a robust spatiotemporal quantification of statistically significant future changes in prescribed burn windows for southeastern Australia. There are significant decreases during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Yet, a lack of longterm, reliable observational record of above ground biomass prohibits the direct use of such key driving variable in the current analysis. Another example involves the effects of sub-grid topography, such as slope, aspect, and terrain ruggedness at a typical scale of several kilometers, on wildfire spread and intensity 63 . Future ESM development are encouraged to incorporate the subgrid topographic factors to improve their representation of wildfire regimes and facilitate better observational constraint.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, a lack of longterm, reliable observational record of above ground biomass prohibits the direct use of such key driving variable in the current analysis. Another example involves the effects of sub-grid topography, such as slope, aspect, and terrain ruggedness at a typical scale of several kilometers, on wildfire spread and intensity 63 . Future ESM development are encouraged to incorporate the subgrid topographic factors to improve their representation of wildfire regimes and facilitate better observational constraint.…”
Section: Discussionmentioning
confidence: 99%
“…In the southeast US, Kupfer et al (2020) used climate models to project that the future frequency of suitable days for prescribed burning will decrease substantially in the summer months by the end of the twenty-first century compared with historical conditions. Similar efforts using regional climate models in Australia have also pointed toward a more constrained burn window in southeast Australia in future climates (Di Virgilio et al, 2020), however, the projections also vary regionally and with definition of suitable conditions for prescribed burning (H. Clarke, Gibson, et al, 2019;Clarke, Tran, et al, 2019). Other work has suggested that suppression capacity could be exceeded more regularly in future due to climate change in parts of Canada (Wotton et al, 2017).…”
Section: Humans Suppress Fire To Protect Lives and Assetsmentioning
confidence: 97%
“…Hazard reduction burns are an adaptation measure that is widely used to reduce forest fire risk in Australia by managing fuel load. Climate change impacts on temperature and fuel moisture in southeast Australia are expected to decrease the capacity to carry out hazard reduction burns in autumn, but increase the ability to carry out these burns in winter instead 115,116 . The importance of fuel dryness in preconditioning forest flammability provides information for early warning and preparedness for extreme fires 117 .…”
Section: Broader Context and Response Optionsmentioning
confidence: 99%